The Effect of Self-Efficacy on Knowledge Sharing Behaviour with Big Five Personality as a Mediator among Employees in a Service Company - Delyani Fatmawina Pulungan; Hasanuddin Hasanuddin; Salamiah Sari Dewi (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
Knowledge sharing behavior is essential in-service organizations, where service quality heavily depends on employees' ability to exchange work experience, job-related information, and practical solutions. This study examines the effect of self-efficacy on knowledge sharing behavior and investigates the mediating role of the Big Five personality dimensions among contract employees at PT Prima Karya Sarana Sejahtera (PKSS) in Medan City. The Big Five personality traits were selected as mediators because personality characteristics influence how employees translate self-efficacy into workplace behaviors, such as knowledge sharing. Adopting an explanatory quantitative design, data were collected from 300 contract employees who had participated in job-related training; the data were subsequently analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that self-efficacy exerts a positive effect on knowledge sharing behavior. Furthermore, all five personality dimensions mediate the relationship between self-efficacy and knowledge sharing behavior, with conscientiousness emerging as the strongest pathway, followed by openness, extraversion, neuroticism, and agreeableness. The novelty of this study lies in the development of a comprehensive mediation model that simultaneously evaluates all Big Five personality dimensions as parallel mechanisms linking self-efficacy to knowledge sharing behavior. These findings contribute to knowledge management and organizational psychology by demonstrating that knowledge sharing is shaped not only by employee confidence but also by personality-driven behavioral mechanisms